56:x-24:x+16
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Bài 1:
\(101\cdot125+101\cdot25-101\cdot50\)
\(=101\cdot\left(125+25-50\right)\)
\(=101\cdot100\)
\(=10100\)
Bài 2:
\(76\cdot115+56\cdot24+59\cdot24\)
\(=76\cdot115+24\cdot\left(56+59\right)\)
\(=76\cdot115+24\cdot115\)
\(=115\cdot\left(76+24\right)\)
\(=115\cdot100\)
\(=11500\)
tính x=\(\sqrt{97-56\sqrt{3}}+\sqrt{52+16\sqrt{3}}\)
y=\(\sqrt{33+20\sqrt{2}}+\sqrt{24-16\sqrt{2}}\)
Ta có: \(x=\sqrt{97-56\sqrt{3}}+\sqrt{52+16\sqrt{3}}\)
\(=\sqrt{49-2\cdot7\cdot4\sqrt{3}+48}+\sqrt{48+2\cdot4\sqrt{3}\cdot2+4}\)
\(=\sqrt{\left(7-4\sqrt{3}\right)^2}+\sqrt{\left(4\sqrt{3}+2\right)^2}\)
\(=\left|7-4\sqrt{3}\right|+\left|4\sqrt{3}+2\right|\)
\(=7-4\sqrt{3}+4\sqrt{3}+2\)
\(=9\)
Làm luôn phần y :D
y = \(\sqrt{33+20\sqrt{2}}+\sqrt{24-16\sqrt{2}}\)
y = \(\sqrt{33+2.10\sqrt{2}}+\sqrt{24-2.8\sqrt{2}}\)
y = \(\sqrt{33+2.5.2\sqrt{2}}+\sqrt{24-2.4.2\sqrt{2}}\)
y = \(\sqrt{25+2.5.\sqrt{8}+8}+\sqrt{16-2.4.\sqrt{8}+8}\)
y = \(\sqrt{\left(5+\sqrt{8}\right)^2}+\sqrt{\left(4-\sqrt{8}\right)^2}\)
y = |5 + \(\sqrt{8}\)| + |4 - \(\sqrt{8}\)|
y = 5 + \(\sqrt{8}\) + 4 - \(\sqrt{8}\) (Vì 4 > \(\sqrt{8}\) nên 4 - \(\sqrt{8}\) > 0)
y = 9
Vậy y = 9
Chúc bn học tốt!
a) \(58+7x=100\)
\(=>7x=100-58\)
\(=>7x=42\)
\(=>x=42:7\)
\(=>x=6\)
b) \(3x-7=28\)
\(=>3x=28+7\)
\(=>3x=35\)
\(=>x=35:3\)
\(=>x=\dfrac{35}{3}\)
c) \(x-56:4=16\)
\(=>x-14=16\)
\(=>x=16+14\)
\(=>x=30\)
d) \(101+\left(36-4x\right)=105\)
\(=>36-4x=105-101\)
\(=>36-4x=4\)
\(=>4x=36-4\)
\(=>4x=32\)
\(=>x=32:4\)
\(=>x=8\)
e) \(\left(x-12\right):12=12\)
\(=>x-12=12.12\)
\(=>x-12=144\)
\(=>x=144-12\)
\(=>x=132\)
f) \(\left(3x-2^4\right).7^3=2.7^4\)
\(=>3x-2^4=2.7^4:7^3\)
\(=>3x-16=2.7=14\)
\(=>3x=14+16\)
\(=>3x=30\)
\(=>x=30:3\)
\(=>x=10\)
i) \(\left(10+2x\right).4^{2011}=4^{2013}\)
\(=>10+2x=4^{2013}:4^{2011}\)
\(=>10+2x=4^2=16\)
\(=>2x=16-10\)
\(=>2x=6\)
\(=>x=6:2\)
\(=>x=3\)
\(#WendyDang\)
8 x 2 = 16 8 x 3 = 24 8 x 4 = 32 8 x 5 = 40
16 : 8 = 2 24 : 8 = 3 32 : 8 = 4 40 : 8 = 5
8 x 6 = 48 8 x 7 = 56 8 x 8 = 64 8 x 9 = 72
48 : 8 = 6 56 : 8 = 7 64 : 8 = 8 72 : 8 = 9
a: =>7x=42
hay x=6
b: =>5x=35
hay x=7
c: =>x-14=16
hay x=30
d: =>36-4x=4
=>4x=32
hay x=8
e: =>x-12=144
hay x=156
f: =>3x-16=14
hay x=10
g: =>x+33=45
hay x=12
h: =>(x+9):2=39
=>x+9=78
hay x=69
a: =>7x=42
hay x=6
b: =>5x=35
hay x=7
c: =>x-14=16
hay x=30
d: =>36-4x=4
=>4x=32